(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
Abstract Gifted learners and their needs are often inadvertently overlooked. Planning for the needs of all students requires deliberate thought including specific goals. Additionally, tested and reliable instructional methods and techniques should be sought out and implemented within our classrooms to meet the needs of students and problem-based learning, PBL, is one such method. PBL is based on ill-structured, open-ended problems; problems that do not have a correct answer. Gifted learners need the type of learning environment that PBL can create in order to utilize their creativeness, improve their critical thinking, and problem-solving abilities. This manuscript includes an overview of how an interdisciplinary approach with PBL can provide a path to increase opportunities for gifted learners to maximize their potential.